2022
DOI: 10.1155/2022/9288452
|View full text |Cite|
|
Sign up to set email alerts
|

Machine Learning-Based Automated Diagnostic Systems Developed for Heart Failure Prediction Using Different Types of Data Modalities: A Systematic Review and Future Directions

Abstract: One of the leading causes of deaths around the globe is heart disease. Heart is an organ that is responsible for the supply of blood to each part of the body. Coronary artery disease (CAD) and chronic heart failure (CHF) often lead to heart attack. Traditional medical procedures (angiography) for the diagnosis of heart disease have higher cost as well as serious health concerns. Therefore, researchers have developed various automated diagnostic systems based on machine learning (ML) and data mining techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 145 publications
0
23
0
Order By: Relevance
“…PPH is a common complication after cesarean section, and uterine weakness is one of the main causes of PPH [ 9 ]. PPH is urgent and develops rapidly, requiring active and effective treatment; otherwise it may cause functional ischemia of multiple organs, hypovolemic shock, etc., and seriously affect the maternal quality of life [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPH is a common complication after cesarean section, and uterine weakness is one of the main causes of PPH [ 9 ]. PPH is urgent and develops rapidly, requiring active and effective treatment; otherwise it may cause functional ischemia of multiple organs, hypovolemic shock, etc., and seriously affect the maternal quality of life [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to data mining, privacy, security, and abuse of information are all major concerns [21]. In [28], several ML techniques for developing automated heart disease detection solutions were examined, unlike earlier studies, which only focused on one methodology. If they're interested in automating the identification of heart disease, they hope this study will be useful.…”
Section: Iirelated Workmentioning
confidence: 99%
“…A large number of algorithms and models have been presented for the diagnosis of cardiac disease. [ 27 ] Potes et al [ 28 ] identified heart sounds with an integrated algorithm and a deep learning algorithm, reaching 86% classification accuracy on the 2016 PhysioNet/CinC Challenge database. Since then, an increasing number of researchers have focused on the identification of cardiac disease using heart sounds.…”
Section: Related Workmentioning
confidence: 99%